Synthesis of 2D Nitrogen-Doped Mesoporous Carbon Catalyst for Oxygen Reduction Reaction - Yu, Zhipeng (Materials (Basel), 2017)
2D nitrogen-doped mesoporous carbon (NMC) is synthesized by using a mesoporous silica film as hard template, which is then investigated as a non-precious metal catalyst for the oxygen reduction reaction (ORR). The effect of the synthesis conditions on the silica template and carbon is extensively investigated. In this work, we employ dual templates—viz. graphene oxide and triblock copolymer F127—to control the textural features of a 2D silica film. The silica is then used as a template to direct the synthesis of a 2D nitrogen-doped mesoporous carbon. The resultant nitrogen-doped mesoporous carbon is characterized by transmission electron microscopy (TEM), nitrogen ad/desorption isotherms, X-ray photoelectron spectroscopy (XPS), cyclic voltammetry (CV), and rotating disk electrode measurements (RDE). The electrochemical test reveals that the obtained 2D-film carbon catalyst yields a highly electrochemically active surface area and superior electrocatalytic activity for the ORR compared to the 3D-particle. The superior activity can be firstly attributed to the difference in the specific surface area of the two catalysts. More importantly, the 2D-film morphology makes more active sites accessible to the reactive species, resulting in a much higher utilization efficiency and consequently better activity. Finally, it is noted that all the carbon catalysts exhibit a higher ORR activity than a commercial Pt catalyst, and are promising for use in fuel cells.